Improve productivity through digital manufacturing - But, Adrian; Canarache, Radu; Gal, Lucian (Journal of Production Engineering, 2023)
In the future the digitalization and "Industry 4.0” will be in every step of the product lifecycle from design to the manufacture, service, and maintenance. Through digitalization, the companies will be able to operate and program the complex CNC machine tools that will be ready to respond more flexibly to the market demands and at the same time to boost their productivity. Work preparation and production can be breaking down further into additional process steps, ranging from tendering to quality assurance. The demand for digitalization solution can be illustrated thru the following targets and questions what every production company must define and establish: 1. How long time will be the part on the machine to be manufacturi; 2. Is that CNC machine tools (what is able and have the technical characteristics) available; 3. Are necessary new cutting tools for this new job; 4.The CNC operator is familiar with the CNC control equipment; 5. Does the workpiece tolerance correspond with the customer specifications. Is not so easy to link up all this requests and to find the best solutions in time and to have high productivity. Digital manufacturing will give us the preliminary units costs and delivery deadline that must be determined to be able to tender for a job correctly. Today, the amount of time a workpiece will require for machining can be calculated quickly reliably and very important, without trial runs, using CNC simulation solutions. This recommendations from our paper can be an answer at the production companies and the advantage of this implementations is that can be made step by step. The solution of this implementation should be in concordance with the company’s requirements and resources.